Building Inclusive Learning Communities in Multicultural Classrooms: The Role of the CTL Model in Learning Interpersonal Skills - Ali, Aisyah; Bektiarso, Singgih; Walukow, Auldry F.; Narulita, Erlia (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This study explores the effectiveness and challenges of implementing the Contextual Teaching and Learning (CTL) model in multicultural classrooms, particularly focusing on its impact on interpersonal skills development. The primary aim is to investigate how the CTL model enhances student engagement by connecting academic content to real-world contexts and to identify the barriers that impede its effective application. This research utilized a qualitative approach with a case study method to examine the application of the CTL (Contextual Teaching and Learning) model in building inclusive learning communities and fostering interpersonal skills in multicultural classrooms. The data collection techniques used in this study included interviews, observations, and document analysis. The findings indicate that while the CTL model significantly enhances student engagement and fosters the development of interpersonal skills, its implementation is fraught with challenges. Key obstacles include insufficient teacher training, misalignment with existing curriculum standards, limited resources, and institutional barriers such as rigid schedules and lack of administrative support. Despite these challenges, the research highlights the importance of sustained professional development and a supportive learning community to overcome these barriers. By addressing these issues, educators can better leverage the CTL model to create inclusive and effective learning environments. Overall, this study underscores the potential of the CTL model to transform teaching practices and improve student outcomes in multicultural settings. It calls for a concerted effort to provide the necessary support and resources for educators to implement the CTL model successfully, thereby enhancing educational experiences and fostering inclusive learning communities.